‘Wretched folk, ready for any mischief’: The South African state’s battle to incorporate poor whites and militant workers, 1890-1939 (Historia, 2021)
Between the 1870s and 1913 the idea took root that South Africa, with the exception of areas of dense African settlement, was a white man’s land, although the white community was only 340 000 strong in the late 1870s in a population of 2,2 million, and just over 1,25 million in a population of 6,4 million in 1915. Most of those who propagated white supremacy accepted that a consolidated white group was needed to dominate the black majority. The main obstacle to such a consolidation was the presence of growing numbers of very poor white people on the land and in the towns and cities.Some were destitute and unemployable; others were unskilled or barely skilled.
Keywords: white supremacy; Anglo-Boer; Alfred Milner; white man’s country; poor whites; emancipated slaves; racial exclusivity; Zuid-Afrikaansche Republiek; education; English-speaking; racially homogeneous; proletariat; Cape Colony; black; coloured; children; commercial farming; illiteracy